Cochlear implantation in children with sickle cell disease. Issue 1 (February 2015) - Ashfield, Thomas; Pai, Irumee; Wilson, Katherine; Britz, Anzel; Connor, Steve; Fitzgerald‐O'Connor, Alec; Jiang, Dan
Abstract Sickle cell disease (SCD) is associated with sensorineural hearing loss (SNHL). Although the hearing loss is usually mild, some develop severe‐to‐profound hearing loss, in whom cochlear implants (CI) may be an option. We present the cases of two children with SCD who developed bilateral severe‐to‐profound SNHL and underwent cochlear implantation. One patient became profoundly deaf after an acute episode of dizziness. Imaging indicated bilateral cochlear ossification, making subsequent cochlear implant surgery challenging. The second patient developed bilateral severe‐to‐profound SNHL following acute vaso‐occlusive crises. She went on to have uncomplicated cochlear implant surgery. These cases illustrate the variable manner in which children with SCD may develop SNHL, and the difficulties associated with managing such cases. We recommend that children with SCD should undergo regular audiological assessment. Furthermore, clinicians should be aware of the risk of cochlear fibrosis and ossification and ensure prompt assessment following an acute vaso‐occlusive crisis or unexplained vestibulocochlear event.